PENGARUH GAYA BELAJAR MATEMATIKA SISWA KELAS X TERHADAP KEMAMPUAN KOMUNIKASI MATEMAMATIS PADA MATERI MATRIKS DI SMK NEGERI 1 TOMA - Buulolo, Wiwin Cintia Dewi (Afore : Jurnal Pendidikan Matematika, 2024)
The objective of this study is to gather empirical data on the impact of several learning methods (visual, auditory, and kinesthetic) on the mathematical communication skills of class X students at SMK Negeri 1 Toma during the 2023/2024 academic year. This study falls under the category of quantitative research. All the participants in this study were 45 students in the X grade at SMK Negeri 1 Toma. The data gathering procedures used in this study consist of questionnaires and tests. The study employs many data analysis approaches, including Classical Assumption Test, Simple Linear Regression Analysis, Partial Determination Coefficient Analysis, and Hypothesis Testing. The study findings indicate that the tcount for the learning style variable (X) is 3,757 with a table value of 1.681, and the significant level is 0.000, which is less than 0.05. Additionally, the coefficient of determination test (R2) yields a value of 0.247, indicating that it has an impact of 24.7%. It can be inferred that the learning style variable (X) has a positive and substantial impact on the student's mathematical communication ability variable, as well as the mathematical communication ability of the whole class. Hence, academics propose doing a comprehensive investigation to scrutinise this event and use it as a point of reference.